DIGITAL SOCIAL SUPPORT FOR PEOPLE WITH CHRONIC ILLNESSES: AN ANALYSIS OF COMMUNICATION DYNAMICS ON SOCIAL MEDIA PLATFORMS - Syafruddin Ritonga; Kisno (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
People with chronic illnesses face significant physical and psychological challenges, making social support an important aspect in improving their quality of life. The development of social media opens up new spaces for digital social interactions that can provide social support. However, the dynamics of communication and the effectiveness of digital social support in the context of chronic illness are still poorly understood comprehensively. This study used a mixed methods approach with quantitative data collection through online questionnaires (n=200) and qualitative data through semi-structured interviews and social media content analysis. Quantitative analysis was conducted with descriptive and inferential statistics, while qualitative analysis used thematic analysis to explore experiences and communication patterns in digital communities. The results of the statistical analysis showed a positive and significant relationship between digital social support and psychological well-being (r = 0.62), disease management motivation (r = 0.58), and user satisfaction (r = 0.65), with p-values ​​<0.001 for all variables. This indicates that adequate digital social support contributes significantly to improving the well-being and motivation of people with chronic illnesses. Qualitative data revealed that emotional and informational support were dominant in community interactions, which were asynchronous and multilateral. However, the risk of misinformation, privacy issues, and negative psychological impacts such as anxiety were also found to be major challenges. The novelty of the study lies in the integration of quantitative and qualitative analysis in the context of digital social support for people with chronic diseases, as well as highlighting the risks of digital communication that have received little attention in previous literature, thus broadening the understanding of digital communication and health theory. Social media has the potential to be an effective means for social support for people with chronic diseases if communication risks can be managed well. The development of safe platform features and digital literacy education are suggested to improve the quality of digital social support, so further research is needed to expand the context and develop adaptive interventions.